Optimizing alternative schemes of community-based breeding programs for two Ethiopian goat breeds - Abegaz, Solomon; Sölkner, Johann; Gizaw, Solomon; Dessie, Tadelle; Haile, Aynalem; Mirkena, Tadele; Getachew, Tesfaye; Wurzinger, Maria (Acta Agraria Kaposváriensis, 2014)
One tier community-based breeding schemes with four different scenarios for Western Lowland and Abergelle goat of Ethiopia were simulated using ZPLAN computer program to compare the genetic gain of the breeding objectives traits across the alternatives. The scenarios were different in terms of numbers of traits in selection criteria while keeping the breeding goals the same throughout the alternatives. Simulation study showed that there was little difference in annual genetic gain for individual breeding objectives traits and annual monitoring gain (aggregate gain) across the different alternatives. The range of 0.8702–0.8724 kg, 0.0001–0.0006 and 0.0184–0.0195% of six months weight, number of kids born and proportion of weaned kids were predicted for Western Lowland goat respectively. For Abergelle goat the range of 0.36–0.3675 kg of six months weight, 0.0066–0.0114 kg of daily milk yield and 0.0068–0.0085% proportion of weaned kids per does per year were simulated. The lowest aggregate genetic gains of 25.94 and 16.42 were obtained for Western Lowland and Abergelle goat respectively from the alternative where only one trait (growth) included in the selection criteria (index or record).
Keywords: Breeding program; Ethiopia; Genetic gain; Goat; selection criteria